The delight of art: Giorgio Vasari and the traditions of humanist discourse - Cast, David (Pennsylvania State Univ. Press, 2009)
"A study based on the text, the Lives of the Artists, by Giorgio Vasari. Discusses how the visual arts in the Renaissance were an occasion for delight or pleasure. Argues that such an attention was encouraged by certain social and intellectual practices"--Provided by publisher